2015
DOI: 10.5812/jjm.16217
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Quinolone Resistance Genes Among Extended-Spectrum B-Lactamase-Producing Escherichia coli in Mashhad, Iran

Abstract: Background:Escherichia coli is an important bacterial species based on incidence and associated infection severity. Some E. coli strains produce extended-spectrum beta lactamase (ESBL) and are called ESBL-producing E. coli. These strains are resistant to most classes of cephalosporin and a number of other classes of antibiotics. Plasmids carrying qnr genes have been found to transmit quinolone resistance.Objectives:The aim of this study was to determine the frequency of qnr genes in ESBL-producing and non-ESBL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
5
4
0
1
Order By: Relevance
“…Our results are in accordance with the study of Bajaj et al, where 50% of CTX-M-producing isolates were positive for the qnrS gene [14]. Co-occurrence of PMQR and other antibiotic resistance genes has been reported in similar studies from China, Iran, and Austria [55,58,59]. The presence of PMQR genes among bacteria is a cause for concern, because these resistance genes are thought to create an optimum environment for selection of chromosomal resistance determinants [60,61].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in accordance with the study of Bajaj et al, where 50% of CTX-M-producing isolates were positive for the qnrS gene [14]. Co-occurrence of PMQR and other antibiotic resistance genes has been reported in similar studies from China, Iran, and Austria [55,58,59]. The presence of PMQR genes among bacteria is a cause for concern, because these resistance genes are thought to create an optimum environment for selection of chromosomal resistance determinants [60,61].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this finding correlated with the results of clinical specimens from SKIMS Kashmir, where 27.1% of AmpC producing isolates were obtained ( Ahmad et al, 2010 ). qnrS gene was obtained in 63% isolates in this study, similarly, the occurrence of PMQR and ESBL genes have been reported in studies from China and Iran ( Li et al, 2014 , Mood et al, 2015 ). We found that the co-existence of bla TEM and heavy metal resistance elements viz.…”
Section: Discussionsupporting
confidence: 87%
“…Isolates having bla TEM were checked for integron analysis using PCR amplification of a conserved segment (CS 3′/5′) along with IntI , Sul1 using published primers ( Galimand et al, 2003 , M73819, U12338) and simultaneously (insertion sequence, transposons) ISecp1, TN3, and TN21 ( Mood et al, 2015 , Sheikh et al, 2014 , Brown et al, 1985 ) were also analyzed using a specific set of primers.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…30 In Mashhad, 200 clinical isolates were studied by Harifi Mood et al and qnrA, qnrB, and qnrS genes were found in 31.5%, 17% and 7% of the isolates, respectively. 31 Vasilaki et al in Greece showed that 11 isolates (10%) carried qnrS gene and none of the isolates harbored qnrA and qnrB genes. 32 The 2 recent studies are in contrast with our results.…”
Section: Discussionmentioning
confidence: 99%